Effect of pathophysiological stressors on the tissue expression of parathyroid hormone-related protein (PTHrP) - Oruqaj, Learta Pervizaj; Justus Liebig University Giessen (My University, 2016)
Myocardial infarction and sepsis are considered as devastating diseases in the world. Myocardial ischemia occurs when blockage of one or more coronary arteries reduces the blood flow to the heart. Thus, the amount of oxygen that myocardium receives decreases. Sepsis is a systemic immune response to the infection caused mostly by bacteria.Therefore, the current study aimed to discover the role of high fat diet and ageing in PTHrP system under ischemia/reperfusion in order to explain the so-called obesity paradox, and the role of hypothermia in vital organs, in particular the cardiac expression of PTHrP under endotoxemia. Results suggest an age-dependent expression of PTHrP, being highly elevated in older mice rather than in adult mice. High fat diet affected the expression of PTHrP, its corresponding receptor and the downstream molecules ADRP and PPARgamma. Ischemia/reperfusion increased the mRNA expression of PTHrP and ADRP in the lung but it had no significant effect on PTH-1R and PPARgamma. Results corroborate the activation of the pulmonary paracrine pathway under stress conditions, especially under HFD. Concerning LPS, it induces the PTHrP system in the lung and liver but temperature alteration did not have any significant impact. Left ventricle revealed opposite results compared to other vital organs as LPS downregulated the mRNA of PTHrP and PTH-1R. To verify the downregulation of the PTHrP system in the heart, in vitro experiments performed in the Langendorff apparatus, and in vivo experiments in pigs showed that hypothermia improved mRNA expression of PTHrP in the heart. Hypothermia improved the PTHrP responsiveness in septic hearts as one of the functional parameters of the heart, the LVDP that represents the cardiac contractility, cell shortening of isolated rat heart cells and phosphorylation of ERK (ERK2) were increased under septic conditions.Therefore, we hypothesize that high fat diet may increase the expression of PTHrP system in the lung under ischemia/reperfusion and thereby may improve the epithelial-mesenchymal paracrine cross talk in the lung, the paracrine loop important for pulmonary function. Increase of leptin and other PTHrP downstream targets may stabilize the pulmonary remodeling after ischemia/reperfusion, which describes the obesity paradox. The current data indicate that hypothermia influences the cardiac expression of PTHrP under septic conditions, which suggests that PTHrP participates in improving the cardiac function in this situation.

Der Myokardinfarkt und septische Ereignisse gehören zu den schwerwiegensten Erkrankungen weltweit. Ein Moykardinfark entsteht, wenn eine oder mehrere Koronargefäße eingeengt oder verschlossen sind. In der Folge wird das Myokard sauerstoffarm. Eine Sepsis ist eine systemische Immunantwort auf eine generalisierte bakterielle Infektion.Aus diesem Grunde wurde in die vorliegenden Studie näher untersucht, welchen Einfluss ein Myokardinfarkt und eine sterile Infektion mit LPS auf die gewebespezifische Expression von PTHrP hat, und ob dies durch fettreiche Diät zur Erzeugung eines obesity paradox oder durch Hypothermie zum besseren Schutz der betroffenen Organe beeinflusst wird.Die Ergebnisse suggerieren eine altersabhängige Expression von PTHrP, die im Alter zunimmt. Eine fetthaltige Diät beeinflusst die Expression von PTHrP, seines Rezeptors und seiner Targetgene ADRP und PPARgamma. In der Folge einer Reperfusion nach myokardialer Ischämie steigt die pulmonale Expression von PTHrP und ADRP aber nicht die des Rezeptors und des PPARgamma. Die Ergebnisse suggerieren eine Aktivierung des pulmonalen PTHrP Systems bei fettreicher Ernährung.In Bezug auf LPS konnte gezeigt werden, dass LPS die pulmonale und hepatische Expression steigert ohne dass eine Hypothermie darauf Einfluss nimmt. Im Gegensatz dazu wurde im linken Ventrikel des Herzens PTHrP herabreguliert. Diese Befunde konnte in vitro und in vivo verifiziert werden und im Herzen kam es unter Hypothermie zu einer Normalisierung der Expression von PTHrP und einer funktionellen Verbesserung. In ähnlicher Weise reagierten isolierte Herzmuskelzellen auf LPS und Hypothermie (Verbesserte lastfreie Zellverkürzung, ERK2-Aktivierung).Aus diesen Befunden lässt sich suggerieren, dass eine fettreiche Ernährung zu einer verbesserten Stimulation des PTHrP-Systems in der Lunge nach Infarktereignissen beiträgt und dass dies zumindest partiell zum obesity paradox beitragen könnte. Ausserdem zeigen die Befunde, dass Hypothermie die kardiale Expression von PTHrP normalisiert und dadurch zu einer verbesserten kardialen Funktion hypotherm exponierten Sepsis-Patienten beiträgt.
Keywords: ddc:610